Identitas Bali Tahun 1930-an dalam Geguritan Matamba ka Jawi dan Geguritan Pamargin I Made Kawi ka Bogor: Kajian Sastra Perjalanan - Dewi, Ni Putu Novsa; Sutjiati Beratha, Ni Luh; Darma Putra, I Nyoman (Humanis; Vol 29 No 1 (2025), 2025)
This study aims to analyze Bali’s identities in the 1930s through traditional Balinese literatures with travel themes, namely Geguritan Matamba ka Jawi ‘Seek medical treatment in Jawa’ and Geguritan Pamargin I Madé Kawi ka Bogor ‘I Made Kawi's Journey to Bogor’ . This research is a qualitative study using Thompson's travel writing theory. The elements of travel writing present that both texts depict complementary portrayal of Bali's identity in the 1930s, such as personal identity, social identities, and cultural identities. Personal identity is depicted through the element of revealing the self, social identities is seen in the representing the other element, cultural identities reflected through the element of reporting the world and element of representing the other. This elements of identities provides understanding of how Balinese expressed their identities during the colonial period, as a topic that rarely explored, while reinforcing the fact that identity and travel writing are closely related.